Influence of cavo superficial enamel acid-etching on the microtensile bond strength of low-shrinkage composite resin - Raquel Devisate BORGHI; Erick Kamiya COPPINI; Josué Junior Araújo PIEROTE; João Victor Frazão CÂMARA; Luis Alexandre Maffei Sartini PAULILLO (Universidade Estadual Paulista, 2020)
Abstract Introduction To prevent the shrinkage stresses produced during polymerization, composite resins of low polymerization shrinkage were developed. Objective To evaluate the microtensile bond strength in class I cavities restored by acid-etching the cavosurface angle and with composite resins indicated for posterior teeth. Material and method 48 healthy molars were selected and divided into six groups (n = 8), considering that the cavosurface enamel of three groups was etched with 35% phosphoric acid. The teeth were restored with the Clearfil SE Bond adhesive system and Filtek Z350 XT, Empress Direct, and Charisma Diamond composite resins, which were light-cured for 40 seconds. After 24 hours, the teeth were taken to a cutting machine, which produced sections in the buccolingual and mesiodistal directions. This resulted in toothpicks of 0.9×0.9 mm that were taken to the universal testing machine for the microtensile bond strength test. Statistical analysis was performed with ANOVA and Tukey's test (p < 0.05). Result There was no statistically significant difference between the groups evaluated. Conclusion Acid-etching the cavosurface angle did not affect the performance of restorations, probably due to the adhesive system used.